Desmosomal vulnerability renders left atria more susceptible to detrimental effects of androgenic anabolic steroids. (24th May 2021) - Sommerfeld, L; Holmes, AP; Kavanagh, DM; Pike, JA; O Shea, C; Cardoso, VR; Kabir, SN; Pavlovic, D; Gehmlich, K; Stoll, M; Gkoutos, GV; Kirchhof, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): CATCH ME Foundation Leducq BACKGROUND: In cardiac myocytes, desmosomal proteins and ion channels form macromolecular complexes important for maintaining cell adhesion and electrical integrity. High serum levels of androgenic anabolic steroids (AAS) promote cardiac muscle growth, but any detrimental impact on atrial gene transcription and/or electrophysiological function is unknown. PURPOSE: To investigate the effects of chronic AAS exposure on atria in a mouse model with desmosomal impairment. METHODS: Young (8-10 week) male wild-type (WT) and heterozygous plakoglobin-deficient (plako+/-) mice were challenged with the AAS dihydrotestosterone (DHT) or placebo for 6 weeks by osmotic mini pumps. RNA sequencing (n = 3-6 atria/group) revealed effects of genotype and DHT on left atrial (LA) transcription. Membrane-localised cardiac sodium channels (Nav1.5) were visualised using direct STochastic Optical Reconstruction Microscopy (dSTORM, n = 5-11 LA/group, 122 cells in total) and clustering of individual molecules was quantified using persistence-based clustering. Patch clamping of LA cardiac myocytes was used to record whole cell sodium currents (n = 4-5 LA/group, 77 cells in total). LA action potentials and conduction velocity were evaluated using microelectrode and optical mapping techniques (n = 5-9 LA/group). RESULTS: DHT increased expression of pro-hypertrophic transcripts, e.g. Igf1, Mtpn, fibrosis-associated transcripts, e.g. Col1a1, Col3a1, Lox and pro-inflammatory transcripts, e.g. Ccl6, C7, in both WT and plako+/- LA. Despite Scn5a transcript levels being maintained, dSTORM identified a 29% reduction (p = 0.042) in the number of Nav1.5 localisations at the membrane of plako+/- DHT LA cardiomyocytes, and 25% fewer localisations (p = 0.005) were found within Nav1.5 clusters, compared to WT DHT. Electrophysiological methods revealed a significant reduction in peak sodium current density, decreased action potential amplitude and conduction slowing in plako+/- LA after exposure to DHT. CONCLUSION: This data suggests that a reduction in plakoglobin expression predisposes atrial cardiomyocytes to detrimental electrophysiological effects of high testosterone levels. This is characterised by a perturbed spatial organisation of Nav1.5, decreased sodium current density and conduction slowing.